Cyber-physical Shooting Gallery: Gamification to Address the IT-OT Gap in Cybersecurity Education (Journal of The Colloquium for Information Systems Security Education, 2023)
While much has been written on the dire need for workers who understand both the IT and OT core concepts necessary to protect the cyber-physical systems of critical infrastructure, practical and specific recommendations for how to meet this need through education and workforce training are lacking. Many of the available programs for teaching cybersecurity of physical systems rely on virtual simulations and students may not encounter relevant physical equipment until they are in the workplace. RADICL’s Cyber-physical Shooting Gallery is a critical missing piece toward a comprehensive system to develop the competent workforce the nation needs. Through a series of cyber-physical capture-the-flag challenges that integrate the Purdue ICS Model with the MITRE ATT&CK framework, the Cyber-physical Shooting Gallery provides an accessible educational model for cyber-physical security education and training.
Keywords: Cyber-physical systems; gamification; OT CTF; cybersecurity; pedagogy; critical infrastructure; Purdue Model; MITRE ATT&CK; PLCs; Raspberry Pi; Arduino; electronics; industrial cybersecurity; workforce development